POSSIBILITIES OF APPLICATION THE PROLONGED FORM VALPROIC ACID AND ANTIOXIDANT IN SECONDARYGENERALIZED SEIZURES (clinical and experimental investigation) - G. G. Avakyan; L. N. Nerobkova; O. M. Oleynikova; T. A. Voronina; G. N. Avakyan; E. I. Gusev (Эпилепсия и пароксизмальные состояния)
Possibilities of application the prolonged form valproic acid and antioxidant in secondary - generalized seizures was investigated in experiment and in clinical study in patients with epilepsy. In rats with cobalt-induced epilepsy their efficacy has been revealed by the suppression of determinant hearth in the cortex, which is as a hypothalamus the leading focus for the developing epileptic system in forming of secondary - generalized seizers. Depakine Chronosphere statistically significantly surpasses Depakine Chrono in activity of removal epileptiform discharges in electrocorticogrammes it was determined optimal daily dose of antioxidant Mexidol and interval between the taking of Depakine Chronosphere and injection of antioxidant. Combination of antioxidant and anticonvulsant promotes greater control of seizures in patients with focal symptomatic and/or cryptogenic epilepsy.